Preface (Физика низких температур, 2007)
This issue of Fizika Nizkikh Temperatur contains the
selected plenary talks presented on the International
Conference «Statistical Physics 2006. Condensed Matter:
Theory and Applications (CMPT06)», 12–15 September,
2006, Kharkiv, Ukraine. The Conference is the follow up
of the «Statistical Physics 2005», Lviv, August 2005 in the
renewed tradition of conferences on Statistical Physics and
related topics, established in Ukraine in the early 70s of the
last century. The Conference was convened at the
B. Verkin Institute for Low Temperature Physics and
Engineering of the National Academy of Sciences of
Ukraine, one of the leading research centers of the field.
The Conference was dedicated to the 90th anniversary
of Ilya Lifshitz, one of the world’s foremost theoretical
physicists in condensed matter.